Urban water disinfection and mortality decline in developing countries - Sonia Bhalotra; Alberto Diaz-Cayeros; Grant Miller; Alfonso Miranda; Atheendar S. Venkataramani (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Historically, improvements municipal drinking water quality contributed significantly to mortality decline in wealthy countries. However, water disinfection has not produced equivalent benefits in developing countries today. We investigate this puzzle by analyzing a large-scale municipal water disinfection program in Mexico in 1991 that dramatically increased access to chlorinated water. On average, we find that the program led to a 37 to 48% decline in diarrheal mortality among children and was highly cost-effective (1,310 per life-year saved). However, age (degradation) of water pipes and insufficient complementary sanitation infrastructure attenuated these benefits. Countervailing behavioral responses, although present, appear to be less important.
Keywords: 330; clean water; chlorination; child mortality; infectious disease; diarrhea; Mexico; cost-effectiveness; sanitation; behavioral responses